Desain Kapasitas Produksi Pabrik Es Optimal untuk Mendukung Aktivitas Nelayan di Selatan Sukabumi - Hermawan Hermawan; Adriana Sari Aryani; Kotim Subandi (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The sustainable management of marine ecosystems and fishery resources is a primary goal of the SDGs (Goal 14). Supporting this objective requires the availability of a cold chain network, including ice factories, to preserve the quality and freshness of fish catches. In the southern coastal area of Sukabumi, particularly Ciwaru Village within the Ciletuh National Geopark, the availability of ice factories remains insufficient. Small fishing vessels (<5 GT) in this area require approximately 6 tons of ice per month. This study aims to design the production capacity of a portable mini ice factory to meet the local ice demand. By considering seasonal patterns, fishing volumes, and fluctuating ice needs, the factory is designed to produce around 788–798 tons of ice per year, with an ice storage capacity of 2 tons. The design utilizes 12 kg ice blocks, adjusted to the vessel sizes commonly used by local fishermen employing one-day fishing methods. The planning results indicate that the establishment of this mini ice factory can address the ice supply shortage in Ciwaru, support the maintenance of fish quality, and enhance the economic value of fishermen’s catches.